2011
DOI: 10.5152/tud.2011.018
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of R.E.N.A.L. nephrometry score in robotic assisted partial nephrectomy

Abstract: Objective: In this study, we evaluated the predictive value of R.E.N.A.L. Nephrometry Score (RNS), a system to standardize the renal tumors according to size, location, and depth, for surgical outcomes of robotic partial nephrectomy. Materials and methods:Twenty-nine cases who underwent robotic partial nephrectomy in two institutions between 2008 and 2010 were included in the study. RNS was calculated from preoperative computed tomography and/or magnetic resonance images by considering tumor size, exophytic/en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This group reported that RAPN is a safe method for masses over 7 cm if the mass is exophytic, and benign with a polar localization. [20] In our study warm ischemia time which was the most significant predictive factor in PN was around 20 minutes in accordance with the medical literature (≤25 mins). [3,5,10,14,19] Lack of any significant difference between the pre-and postoperative serum creatinine levels of our patients can be evaluated as an indicator of the appropriateness of the procedure we performed in terms of warm ischemia times.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This group reported that RAPN is a safe method for masses over 7 cm if the mass is exophytic, and benign with a polar localization. [20] In our study warm ischemia time which was the most significant predictive factor in PN was around 20 minutes in accordance with the medical literature (≤25 mins). [3,5,10,14,19] Lack of any significant difference between the pre-and postoperative serum creatinine levels of our patients can be evaluated as an indicator of the appropriateness of the procedure we performed in terms of warm ischemia times.…”
Section: Discussionsupporting
confidence: 90%
“…According to this group, high scores are related with longer warm ischemia times. [20] In our series of 45 patients, the patients' age, gender, sizes of renal masses, renal nephrometry scores, and pathologic characteristics were generally in accordance with the medical literature. Although RAPN was preferred more among patients with small renal masses (≤4 cm), we have performed RAPN on masses greater than 4 cm in our 15 (T1a and T2) patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[26] In another study where predictive value of R.E.N.A.L nephrometry score was analyzed, a strong correlation was observed between R.E.N.A.L nephrometry score, and duration of warm ischemia. [27] Limited warm ischemia time is very well known to be associated with reversible impairment of renal functions. Priorly warm ischemia time below 30 minutes was thought to be compatible with complete recovery of renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Minimally invasive surgery is increasingly being applied in the management of adrenal and renal masses, including laparoscopic [3][4][5][6][7] and robot-assisted laparoscopic approaches. [8][9][10][11][12][13][14][15] Here we present a challenging case of synchronously detected right adrenal and left renal masses resected via sequential robotic right adrenalectomy and zero ischemia off-clamp left partial nephrectomy.…”
Section: Introductionmentioning
confidence: 99%